MUCOCUTANEOUS MANIFESTATIONS FOLLOWING CHEMOTHERAPY IN PEDIATRIC MALIGNANCIES - Rajashekar, Sudarshan; Kuruvila, Maria; Bhat, Kamalakshi; Bhaskaran, Unnikrishnan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Chemotherapy causes destruction of neoplastic cells and rapidly proliferative normal cells leading to significant mucocutaneous changes. The aim of the present study was to determine the postchemotherapeutic mucocutaneous manifestations in pediatric malignancies. Methods: In this cross-sectional study, 63 children with malignancy undergoing chemotherapy over 2Â½ years were examined carefully and followed up for 6 months. A comprehensive clinical history was taken. Detailed systemic and dermatological examination was carried out in the subjects at the time of enrollment. Dermatological examination was performed subsequently at 3-6 months and whenever child presented with any symptoms to the outpatient department. The chemotherapy-induced alopecia (CIA) and pigmentary changes of skin and nails were graded using OSLEN CIA, National Cancer Institute pigment changes and nail changes' grading scales. Results: Males (41 [65%]) outnumbered females (1.8:1). Acute lymphoblastic and myelogenous leukemia were noticed in 38 (60.3%) and 8 (12.6%) patients, respectively. Alopecia (43 [68.3%]) was common with predominant grade 3 (22 [34.92%]). Hair regrowth was noticed in 53 (83.7%) patients within 6 months. Cutaneous linear pigmentary lines, ichthyosis, acral pigmentation, skin peeling, and mucositis were observed in 13 (21%), 10 (16%), 10 (16%), 7 (11%), and 9 (14.28%) patients, respectively. Among total 56 cutaneous infectious manifestations, viral infections include 4 cases of Herpes Zoster, single case of extensive molluscum contagiosum and Varicella. Tinea faciei was recurrent and poorly responsive to treatment. The common nail changes noted were Muehrcke's lines and melanonychia (26 [41.26%]). Conclusion: Alopecia in 43 (68.3%) patients though distressing was reversible in 53 (83.7%) patients. Infections were extensive, recurrent, and required aggressive treatment. Keywords: Chemotherapy, Pediatric malignancies, Cancer.